ARABIC MATERIAL DEVELOPMENT DESIGN FOR SENIOR HIGH SCHOOL - Shafruddin Tajuddin; Muhammad Kamal; Zuryati Zuryati (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2019)
The aims of the research were to develop Arabic learning material model for the senior high school level which was able to become a standard textbook in Arabic learning for high school. It was a realization of the National Language Politics policy that stated, Arabic as a language of religion and culture is taught from elementary school to university level. The research used to research and development (R & D) approach that refers to Borg and Gall theory. There are 10 steps in the development research cycle. However, it was given the small-scale research, which developed materials and media Arabic learning in Jakarta area, this research did at the stage of getting the final product, namely the prototype of Arabic learning material developed. The research was begun through survey research to obtain an empirical sequence of Arabic learning as a basis to support rational empirical strategies in the development design of Arabic learning materials in high school. This research produced Arabic learning textbooks of class X to class XII at the High School level which are equipped with media.